Copper-catalyzed oxidative cross-dehydrogenative coupling (CDC) reaction of alcohols with secondary phosphine oxides. (8th June 2022) - Hua, Yingxiang; Lin, Yanchao; Chen, Wenyi; Ye, Liyi; Yin, Yingwu; Gao, Yuxing; Tu, Song
Graphical abstract: Abstract: A copper-catalyzed oxidative cross-dehydrogenative coupling (CDC) strategy of secondary phosphine oxides and alcohols for the synthesis of various phosphinate esters was proposed. Under the mild reaction conditions (CuCl2 ·2H2 O/K2 S2 O8, at room temperature for 3–12 h under air), a variety of substrates were well-tolerated and afforded the desirable compounds in moderate to excellent yields.